COMPARISON OF ANTI-DIARRHEAL ACTIVITY OF METHANOL AND ETHANOL EXTRACTSS OF WATERMELON RIND(CITRULLUS LANATUS L.) IN WHITE MICE (MUS MUSCULUS) - Nasruhan Arifianto; Munawaroh; Ermawati; Wahyuni (Pharmacy Program, Faculty of Medicine, UPN Veteran Jakarta, 2022)
Watermelon (Citrulluslanatus L.) is one of the most abundant fruit-producing plants in Indonesia. Watermelon is generally only consumed on the red flesh, while the rind is less desirable so that it becomes waste. The purpose of this study was to comparison of anti-diarrheal activity of methanol and 70% ethanol extractss of watermelon rind (citrulluslanatus l.) in white miice (musmuscucolus. This study used a protection method with the induction of MgSO4 (Magnesium Sulfate) by calculating the frequency of diarrhea, changes in stool consistency and stool weight. The data obtained from the activity test results of the watermelon rind methanol extracts against white mice were statistically analyzed using the one-way ANOVA test.Methanolic and 70% ethanolicextractss of watermelon rind (Citruluslanatus L.) contain tannin compounds that have antidiarrheal activity against mice (Musmusculus). From the results of the one-way ANOVA test, the weight of feces, the frequency of diarrhea and the consistency of the stools in the methanol extracts of watermelon rind at a dose of 100 mg/KgBW gave an optimal effect, because the weight of the feces obtained a value of p = 0.633, the frequency of diarrhea obtained a value of p = 0.899 and the consistency of the fecesobtained a value of p = 0.899 p-value = 0.525 compared to the positive control (loperamide). Ethanol extracts of Citrulluslanatus L. had antidiarrheal effect at a dose of 100 mg/kgBW, 200 mg/kgBW, and 300 mg/kgBW. Based on the results of the One Way ANOVA statistical test, the ethanolicextracts of Citrulluslanatus L. had an antidiarrheal effect at a dose of 100 mg/kgBW and the best dose was a dose of 300 mg/kgBW which was significant with the positive control group loperamide P value = 0.000, meaning that the ethanolicextracts of Citrulluslanatus L. at a dose of 300 mg/kgBW had almost the same effect as the loperamide positive control group based on the parameters of stool weight, frequency of diarrhea, and stool consistency. From this data 70% Ethanolic extracts better than methanolicextracts for antidiarrheal activity in mice.